Minireview: Genetic basis of heterogeneity and severity in sickle cell disease. Issue 7 (April 2016) - Habara, Alawi; Steinberg, Martin H
Sickle cell disease, a common single gene disorder, has a complex pathophysiology that at its root is initiated by the polymerization of deoxy sickle hemoglobin. Sickle vasoocclusion and hemolytic anemia drive the development of disease complications. In this review, we focus on the genetic modifiers of disease heterogeneity. The phenotypic heterogeneity of disease is only partially explained by genetic variability of fetal hemoglobin gene expression and co-inheritance of α thalassemia. Given the complexity of pathophysiology, many different definitions of severity are possible complicating a full understanding of its genetic foundation. The pathophysiological complexity and the interlocking nature of the biological processes underpinning disease severity are becoming better understood. Nevertheless, useful genetic signatures of severity, regardless of how this is defined, are insufficiently developed to be used for treatment decisions and for counseling.